Law and Politics - Muhammad Irsyad (International Journal Reglement & Society (IJRS), 2022)
Politics is a power game. Even in a lawless society (law of the jungle), poor and low culture, politics still exists. It contains all the ways to increase the power of individuals or groups. Law is the institutionalization of rules. When the community realizes that the power of each individual needs to be controlled by law, the rights and obligations are not determined by those in power, but by those who are jointly recognized as a truth. Legal justice and social justice are two justices that are compatible with each other but sometimes clash with each other because of a view of values, morals, feelings and the social side of humanity. Like the example of demolition of street vendors, on the one hand, seeing that it has shown legal justice, but on the other hand it shows injustice from the social and humanitarian aspects because it prevents these traders from making fortune by selling business along the roadside. Understanding justice is indeed difficult, like looking for a needle in a deep ocean. Therefore justice is very subjective, depending on how we view it